Về việc đổi mới phương pháp dạy - học cụm từ cố định tiếng Pháp - Nguyễn, Hữu Thọ (H. : ĐHQGHN, 2017)
The reality of teaching French reveals that students have still met with many difficulties in accepting fixed phrases. Hence, It’s an urgent problem to do research on teaching method. This article presents the result of study carried out on the students of French Department-CFL-VNU in April 2006. To compile a textbook of fixed phrases ( may be taught as an optional subject ), to teach phenomena of these fixed phrases right from the beginning of the first year in the form of integration, to carry out analyzing pre-pedagogy in order to determine suitable means of semantics, to instruct students to do scientific research in this field of monolingual language and contrast, to provide students with necessary sources of learning materials, these are main pedagogical proposals dealt with by the author.